Mobility of research workers and knowledge diffusion as evidenced in patent data: the case of liquid crystal display technology - Michael Stolpe (Kiel Institute of World Economics (IfW), 2001)
This paper analyses the nature of knowledge spillovers from research and development (R&D) in the field of liquid crystal display technology by estimating the impact of inventors' changing organizational and collaborative affiliations on the probability of citations in US patents filed between 1976?1995, while controlling for geographic localization effects. It is argued that technology policy towards a particular industry must take the role of inventors' mobility in facilitating the flow of ideas across space and innovating organizations into account. Policy implications for the display industry are discussed against the background of previous experiences with government-sponsored R&D collaborations.
Keywords: L63; O31; O33; O34; 330; knowledge spillovers; liquid crystal displays; R&D collaboration; technology policy; patent citations; Wissenschaftler; Industrielle Forschung; Arbeitsmobilität; Brain Drain; Wissenstransfer; Spillover-Effekt; Patent; Optoelektronische Industrie; Forschungskooperation; Forschungs- und Technologiepolitik; Schätzung; USA